Application of gamma process to two-agent combinations with delayed toxicity. Issue 1 (2nd January 2021) - Yada, Shinjo; Hamada, Chikuma
Abstract: Phase I trials investigate the drugs used on humans for the first time. In cancer treatment, drug safety is examined based on the toxicity. Herein, we propose a dose-finding method for oncological phase I drug combinations with delayed toxicity. The toxicity data of the patients who do not complete the follow-up period and do not experience toxicity are considered missing data. We use data augmentation to impute missing data while modeling the time required to experience toxicity using a hazard function, modeled using a gamma process. Simulation results demonstrate that the proposed method shortens trial durations without affecting performance.